Screening And Characterization Of Starch Produced From Marine Microalgae Klebsormidium Flaccidum Gn-2 - Ramli, Rozi Nuraika (2021)
Starch is the main component that belongs to two third of the human diet pyramid and another one third of starch is used in non-food applications such as biofuel and bioplastic. Products produced from starch are biodegradable and help in reducing the environment pollution. However, environmental problem such as deforestation and shortage of food will eventually happen if the demands of starch from non-food and food products increase. Simultaneously, crops using as feedstocks for biofuel will result in food versus fuel implication. To resolve this problem, the attentions of researchers have been driven towards microalgae. The easy growing and environmentally friendly microalgae has opened a new potential of revolution for starch-based product. In this research two strains of marine microalgae have been successfully isolated and screened from Penang Sea. Based on morphological and molecular identification, these 2 strains are designated as Klebsormidium flaccidum GN-2 and Nannochloropsis oculata YG-2. K. flaccidum GN-2 produced 16.84% of starch and 0.81 g/L biomass while, N. oculata YG-2 produced 3.06% and 0.40 g/L ofstarch and biomass, respectively. Microalgae K. flaccidum GN-2 was chosen for optimization using Response Surface Methodology (RSM) to increase production of starch since it yield higher starch than Nannochloropsis oculata YG-2. The starch produced was 19.06% under the optimized conditions of 35.53 ppt salinity, 23 hours of light exposure and flow rate of 1 v/v of carbon dioxide.